2014
DOI: 10.1038/nrclinonc.2014.159
|View full text |Cite
|
Sign up to set email alerts
|

The development of immunoconjugates for targeted cancer therapy

Abstract: Immunoconjugates are specific, highly effective, minimally toxic anticancer therapies that are beginning to show promise in the clinic. Immunoconjugates consist of three separate components: an antibody that binds to a cancer cell antigen with high specificity, an effector molecule that has a high capacity to kill the cancer cell, and a linker that will ensure the effector does not separate from the antibody during transit and will reliably release the effector to the cancer cell or tumour stroma. The high aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 105 publications
(122 reference statements)
0
62
0
Order By: Relevance
“…Hormonal therapy is limited in the scope of tumors perturbed by such intervention, and such protocols have a low, but notable risk of potentiating other malignancies in addition to inducing an initial surge in tumor growth [2,3]. In the case of immunotherapy, tumors are not homogeneous in their cell surface protein expression, and it is possible that some cells lack the required epitope, or inadvertently shed the required antigen if it is unnecessary for cell survival [4][5][6][7]. Kinase inhibitors enable the clinician to select for patient malignancies that rely on specific aberrantly expressed pathways, but are often toxic to normal cells based on the requirement of these signals for homeostatic functions [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal therapy is limited in the scope of tumors perturbed by such intervention, and such protocols have a low, but notable risk of potentiating other malignancies in addition to inducing an initial surge in tumor growth [2,3]. In the case of immunotherapy, tumors are not homogeneous in their cell surface protein expression, and it is possible that some cells lack the required epitope, or inadvertently shed the required antigen if it is unnecessary for cell survival [4][5][6][7]. Kinase inhibitors enable the clinician to select for patient malignancies that rely on specific aberrantly expressed pathways, but are often toxic to normal cells based on the requirement of these signals for homeostatic functions [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Current using a ligand of an accessible tumor antigen to selectively transport toxins into antigen-expressing neoplastic lesions, the therapeutic efficacy of cell-killing agents can be increased whilst reducing their side effects [34,35].…”
Section: Gc-205mentioning
confidence: 99%
“…As an alternative to direct inhibition approaches, the highaffinity interaction of CAIX ligands with their cognate target can be exploited for the targeted delivery of potent cytotoxic drugs into solid tumors [34,35]. Clinically used cytotoxic drugs in their 'naked' form often do not reach solid tumors in high quantities but accumulate in healthy organs [36], where they can cause severe side effects.…”
Section: Caix As a Target For Drug Deliverymentioning
confidence: 99%
“…Thus, development of novel treatment options is desperately needed. Based on the knowledge of molecular and genetic changes in the development of solid cancer, the molecular targeting agents have been found critical for cancer therapy [1]. Recently, some studies have shown that keratinocyte growth factor receptor (KGFR) is important for cancer therapy [2].…”
Section: Introductionmentioning
confidence: 99%